Tahlil Syi’ir Ta’widzat li Madaini al-Ghazali fi Mausu’ah Syi’ir al-Masrah wa al-Maraya li Adonis (Dirasah Tahliliyah Simiyaiyah ‘inda Michael Riffaterre) - Aprilianing Tyas Tri Tungga Dewi (Journal of Arabic Literature (JaLi), 2022)
This research aims to find out the meaning by reading the heuristics and hermeneutics contained in the poem Ta'widzat limadaini al-Ghazali by Adonis in Riffaterre's semiotic studies. The method of research used is a descriptive qualitative. The primary data source used is the text of the poem Ta'widzat limadaini al-Ghazali in the anthology al-Masrah wa al-Maraya by Adonis. Reading and note-taking techniques were used to collect data in this study. The data analysis method is descriptive analysis using Riffaterre's semiotic theory. The results obtained in this study include (1) finding the meaning of heuristic reading in the poem Ta'widzat limadaini al-Ghazali by Adonis on the title Jasad al-Hashah which contains the journey of a new life of a woman who is small and has no strength. In the title Lau Sakanti implies presupposition and regret 'I' for the choice of a woman's life. While in the title al-Qaidah is a description of the discovery of the essence of new life that is used as a guide. (2) Hermeneutic reading in the title "Jasad al-Hashah", the poet tells the journey of a woman who is helpless, The poem "Lau Sakanti" is a form of regret for 'you' who did not choose and live a life according to the advice of 'I' to achieve the essence the highest. "Al-Qaidah" is that in his stanza the poet gives a picture of someone who is looking for rules so as not to become a group with bound and backward thoughts. The rules of life are found and used as guidelines for living a more advanced life. Adonis' discourse is based on duality (dismantling and construction), namely the destruction of the old cultural heritage, and the quest to rebuild a new Arab culture. Adonis seeks to replace the fixed with the changing, the old with the new, the rigid with the moving, and the finite with the infinite.